Iconography analysis of flower and animal ornaments on the prabhamandala of Shiva statue of the National Museum Indonesia: Analisis ikonografi ornamen bunga dan binatang pada prabhamandala arca Siwa koleksi Museum Nasional Indonesia - Murdihastomo, Ashar (Berkala Arkeologi, 2021)
Shiva is one-third of the highest Gods in Hindu religion, who together with Brahma and Vishnu form Trimurti. The worship of Shiva is embodied in the form of lingga or a statue, decorated with distinctive ornaments and attributes commonly depicted to identify Shiva. A statue with inventory number 29a/3184 in the National Museum Indonesia depicts Siwa with flower and animal ornament which have never been found in other Shiva statues. This article aims to investigate the religious concept flourished during the making of this statue by conducting an iconographic analysis on the said ornaments. Through a descriptive-explanatory approach, the author suggests that the Indian lotus (padma) and goose (hamsa) ornaments are the representation of Shaiva Siddhanta rite practiced during XIII-XIV century CE in the eastern Java.